Islamic Perspective on the Basic Concepts of Ethics - Nasir, Muhammad; Marudin, Marudin (The International Journal of Education Management and Sociology, 2022)
This article will explain the basic differences between the concept of behavior governed by ethics and akhlak, as well as other concepts that also govern human behavior, such as morals and susila. The method used is library research, and the focus of the study is Islamic Perspective on the Basic Concepts of Ethics. The research results show that; 1) The Equation of Ethics, Morals, Susila and Akhlak are them talking about it a). the concept of good and bad behavior, b) human principles to measure or measure human dignity, c) can change according to education, exemplary, habituation and environmental influences. 2) Differences in Ethics, Morals, Susila and Akhlak are found in the term morals which measure the good and bad of a behavior that comes from Allah SWT. whose truth is absolute, while the terms ethics, morals and decency are principles of human behavior originating from the reflections of the human mind (ethics) and the agreement of a society (moral and susila) whose truth is relative. 3) Islamic ethics originates from the Qur'an and Hadith, the good and bad of a behavior have been determined by Allah and additional sources can also be through Ijma' and Qiyas.